Evolution and competition between chiral spin textures in nanostripes with D2d symmetry - Jena, Jagannath; Gobel, Borge; Kumar, Vivek; Mertig, Ingrid; Felser, Claudia; Parkin, Stuart (Science Advances, 2020)
Chiral spin textures are of considerable interest for applications in spintronics. It has recently been shown that magnetic materials with D2d symmetry can sustain several distinct spin textures. Here, we show, using Lorentz transmission electron microscopy, that single and double chains of antiskyrmions can be generated at room temperature in nanostripes less than 0.5 μm in width formed from the D2d Heusler compound Mn1.4Pt0.9Pd0.1Sn. Typically, truncated helical spin textures are formed in low magnetic fields, whose edges are terminated by half antiskyrmions. These evolve into chains of antiskyrmions with increasing magnetic field. Single chains of these objects are located in the middle of the nanostripes even when the stripes are much wider than the antiskyrmions. Moreover, the chains can even include elliptical Bloch skyrmions depending on details of the applied magnetic field history. These findings make D2d materials special and highly interesting for applications such as magnetic racetrack memory storage devices.
CRIS-Team Scopus Importer:2022-04-14